2017
DOI: 10.1038/srep42579
|View full text |Cite
|
Sign up to set email alerts
|

Pnc1 piggy-back import into peroxisomes relies on Gpd1 homodimerisation

Abstract: Peroxisomes are eukaryotic organelles that posttranslationally import proteins via one of two conserved peroxisomal targeting signal (PTS1 or 2) mediated pathways. Oligomeric proteins can be imported via these pathways but evidence is accumulating that at least some PTS1-containing monomers enter peroxisomes before they assemble into oligomers. Some proteins lacking a PTS are imported by piggy-backing onto PTS-containing proteins. One of these proteins is the nicotinamidase Pnc1, that is co-imported with the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Furthermore, we have previously shown that replacing the active site residue lysine 245 with alanine, has a deleterious effect on activity. Although the mutant is stably expressed 18 and targeted to peroxisomes to a similar extent as wild type Gpd1p-GFP (Fig. 3D ), expression of Gpd1p K245A-GFP was unable to restore lysine biosynthesis in mdh3/gpd1Δ cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, we have previously shown that replacing the active site residue lysine 245 with alanine, has a deleterious effect on activity. Although the mutant is stably expressed 18 and targeted to peroxisomes to a similar extent as wild type Gpd1p-GFP (Fig. 3D ), expression of Gpd1p K245A-GFP was unable to restore lysine biosynthesis in mdh3/gpd1Δ cells (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Our study emphasises a central role of peroxisomes in the regulation of NAD + metabolism. Gpd1p co-imports the nicotinamidase Pnc1p 13 , 18 , 28 . Its role inside peroxisomes is unclear as was the role of Gpd1p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, polypeptides with no peroxisomal targeting signal can enter peroxisomes while bound or 'piggy-backed' to polypeptides that contain one. This workaround mechanism was first demonstrated for thiolase (Glover et al, 1994), and evidence has since accumulated that this mechanism is widespread in S. cerevisiae (Yang et al, 2001;Effelsberg et al, 2015;Kumar et al, 2016;Saryi et al, 2017) and other species (Titorenko et al, 2002;Lee et al, 1997). Therefore, we tested whether the observed import of Fox2-GFP and Cta1p-GFP, which had their C-termini blocked with a GFP tag, might be due to the formation of complexes with the respective endogenous native proteins.…”
Section: Comparison Of the Pts1-independent Peroxisomal Import Efficimentioning
confidence: 88%
“…To date, only two proteins with functional PTS2 sequences have been identified in S. cerevisiae, 3-ketoacyl-CoA thiolase (Fox3p/Pot1p) (Erdmann, 1994) and glycerol-3-phosphate dehydrogenase (Gpd1p) (Jung et al, 2010). Curiously, the import of the nicotinamidase Pnc1p into peroxisomes also depends on the PTS2 signal, but it relies on the signal in Gpd1p via a piggy-back import mechanism (Effelsberg et al, 2015;Kumar et al, 2016;Saryi et al, 2017), another feature that is characteristic of peroxisome biogenesis.…”
Section: Introductionmentioning
confidence: 99%